2010
DOI: 10.1002/bbb.249
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact assessment of energy crops cultivation in Europe

Abstract: The production of energy crops must be studied and evaluated in terms of environmental impact, in order to integrate them into a sustainable agricultural development. As bioenergy carriers they offer ecological advantages over fossil fuels by contributing to the reduction of greenhouse gases and acidifying emissions. However, there could be ecological shortcomings related to the intensity of agricultural production. There is a risk of polluting water and air, losing soil quality, enhancing erosion, and reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 34 publications
2
57
0
2
Order By: Relevance
“…Owing to its shallow and extensive root network and its ability to accumulate heavy metals and other pollutants, willow and poplar SRC may be used for remediation of contaminated land and treatment of wastewater (Börjesson 1999a;Rosenqvist and Dawson 2005). The same was also reported for other energy crops, such as Miscanthus, giant reed, hemp, sorghum and sunflower (Fernando et al 2010, and references within).…”
Section: Halting Degradation and Reclaiming Landmentioning
confidence: 74%
See 2 more Smart Citations
“…Owing to its shallow and extensive root network and its ability to accumulate heavy metals and other pollutants, willow and poplar SRC may be used for remediation of contaminated land and treatment of wastewater (Börjesson 1999a;Rosenqvist and Dawson 2005). The same was also reported for other energy crops, such as Miscanthus, giant reed, hemp, sorghum and sunflower (Fernando et al 2010, and references within).…”
Section: Halting Degradation and Reclaiming Landmentioning
confidence: 74%
“…Water footprints might thus arise from the use of an area for bioenergy and from feedstock processing, potentially leading to conflicts with other types of land use or (non-marketable) ecosystem services if water is scarce (Bhardwaj et al 2011;Fritsche et al 2010). Therefore, water-demanding energy crops should be allocated to regions with high effective water availability (Fernando et al 2010). …”
Section: Water Footprintmentioning
confidence: 99%
See 1 more Smart Citation
“…This has resulted in a scattering of decentralised bioenergy plants across the landscape, mainly due to their dependency on spatially diffuse biomass resources. Such configurations of biomass and bioenergy technologies in the landscape make the influence of bioenergy production obvious to the eye (e.g., maize and biogas plant dominated landscapes [4]) and thus open to scrutiny for a broad list of potential environmental burdens 1 , to soil, to water, and land use [5][6][7][8]. In general, life cycle assessment (LCA) is the most popular assessment approach used for investigating the environmental burdens associated with bioenergy production [9][10][11].…”
Section: Assessments Of Bioenergy Systemsmentioning
confidence: 99%
“…1), they identified three regional contexts which have been used to frame regionally focused life cycle thinking. With many burdens of bioenergy production strongly influenced by the regional variability (e.g., management, climate, soil) of biomass production [5,6,23,24,[26][27][28], O'Keeffe et al [19] identified the need to begin determining what is happening "within" a regional context for a bioenergy producing region. They also identified that life cycle thinking framed in a regionally contextualised manner is at a nascent stage, particularly with regard to implementing a suitable or appropriate life cycle impact assessment phase 4 .…”
Section: Regionally Contextualised Life Cycle Thinkingmentioning
confidence: 99%